Language and content 'integration': the affordances of additional languages as a tool within a single curriculum space. Issue 3 (3rd May 2016) - Cross, Russell
Abstract: 'Language across the curriculum' has been pivotal in establishing a knowledge base on the role of language for accessing opportunities afforded by the curriculum. Yet, the ubiquity of language within all facets of human activity – not least of all the more abstract domains of thinking and relating with others – can easily obscure its perceptibility as an object for research relative to other priorities; especially when the curriculum focus is directed towards content-oriented areas, such as mathematics or the humanities. This paper uses an ecological framework to consider the place of language when the teacher's focus is not solely on language, or content, but is equally attentive to both through a relatively new approach to theorizing learners' non-native language within the curriculum: content and language integrated learning. In particular, it critically examines the notion of 'integration' as a pedagogical assumption for working with language in curriculum domains by focusing on teachers' perceptions of the affordances of language as a meditational tool within the classroom space. Findings raise new implications for understanding the role of language(s) within the curriculum, and are significant for addressing the needs of a changing, globalized student demographic where the presence of multiple languages will increasingly shape learners' engagement with the curriculum.